English Pragmatic Competence of Col Language Speakers in Using Expressive and Commissive Acts at Lubuklinggau - Yani Zahra; Sastika Seli; Dewi Syafitri (EDULIA: English Education, Linguistic and Art Journal, 2023)
This research aimed to explain the English Pragmatic Competence of Col language speakers in using expressive and commissive acts and to find out the extent to which Col language pragmatic competence influence the production of English pragmatic competence in expressive and commissive acts. The method used descriptive qualitative. The research subjects were 20 students who studied English consisting of students, collage students and graduates at Lubuklinggau. The data were collected by using questionnaire and pragmatic competence test. After that, the data were analyzed with description. From tests conducted by researcher, informants answered all tests according to different situations. The pragmatic competence of Col language speakers in using expressive and commissive acts, most of them understand that. Of all the expressions, there is no significant negative transfer from L1 and L2 production to English because all percentages are below 50%, which means they don't influence in English pragmatic production. In conclusion, Col speakers understand the use of appropriate expressions in different situations, namely in formal and informal situations. Keywords: Col Language Speakers, Commissive Act, Expressive Act, Pragmatic Competence